Modeling Socio-Economic Consequences of COVID-19: An Evidence From Bibliometric Analysis - Ansari, Yasmeen; Arwab, Mohd; Subhan, Mohammad; Alam, Md Shabbir; Hashmi, Nazia Iqbal; Hisam, Mohammed Wamique; Zameer, M. Nasir (Frontiers in Environmental Science, 2022)
COVID-19 has completely transformed socio-economic activities and our daily lives. The present study provides a comprehensive overview of published literature related to the COVID-19 and socio-economic consequences from the year of 2020 to 2022 using bibliometric approach. This study reviewing 1807 published articles extracting from the SCOPUS database. All considering the published article categorized with the yearly publication, most-cited authors, most-cited journals, most-cited collaborators and most-cited countries. Moreover, different clusters have been demonstrated on the basis of maximum using keywords, authors, and countries and emerging trends in the field of education. Additionally, this study represents a graphical visualization of the bibliometric analysis using VOSviewer and R studio software. A coupling map and three-field plot also have been used for directions for future research. The findings of the study exhibit the consistent pace of publications, most of which focused on education sector and USA moving ahead followed by Saudi Arabia in this domain. Many emerging keywords used, such as socio-economic activities, COVID-19, human and pandemic etc. The results exhibited that COVID-19 has been also associated with different terms included social-media, higher education, environment and health. However, this study provides an extensive summary on recent published work from 2020 to 2022 on COVID-19 and E-learning.